Iedzīvotāju līdzdalība atkritumu šķirošanā ilgtspējīgas attīstības kontekstā - Kapeļka, Agnija (Latvijas Universitāte, 2009)
Eiropas Savienība ir definējusi atkritumu apsaimniekošanu kā prioritāti ilgtspējīgas attīstība nodrošināšanā. Iedzīvotāju līdzdalība atkritumu šķirošanā ir viens no mehānismiem, kā to panākt. Līdz ar to maģistra darba mērķis bija noskaidrot iedzīvotāju līdzdalību atkritumu šķirošanā Rīgas pilsētā. Pētījumā gaitā tika veikta iedzīvotāju reprezentatīva kvantitatīvā aptauja ar mērķi noskaidrot, cik daudz iedzīvotāju šobrīd aktīvi piedalās atkritumu šķirošanā, kā arī noteikt galvenās barjeras dalībai atkritumu šķirošanā. Tāpat tika veiktas ekspertu intervijas ar nozares speciālistiem, pārvaldes un NVO pārstāvjiem ar mērķi gūt padziļinātu izpratni par atkritumu apsaimniekošanas galvenajām problēmām ilgtspējīgas attīstības kontekstā. Savukārt ar iedzīvotājiem tika veiktas padziļinātās daļēji strukturētās intervijas. Galvenā pētījuma atziņa sakņojas idejā, ka Rīgas iedzīvotāju līdzdalība atkritumu šķirošanā šobrīd ir salīdzinoši zemā līmenī, kas saistās ar pilsētas pasīvo ilgtspējīgas atkritumu apsaimniekošanas gaitu. Atslēgas vārdi: atkritumu šķirošana, iedzīvotāju līdzdalība, videi draudzīga uzvedība, ilgtspējīga attīstība.

European Union has settled waste management as one of the main principles how to reach sustainable development. There are increasing debates about citizens as active agents in reaching sustainability by practicing pro-environmental behavior. Participation in recycling is considered as one of the way towards sustainability. Latvia as member of EU should also reach EU directives of the waste management and in order to understand how close it is towards sustainability and how active are citizens taking part in recycling, there was conducted a research “Citizens’ participation in recycling in the context of sustainable development’. There were used both quantitative and qualitative methods in order to gain deeper understanding in the given issue. The target group was chosen – citizens of Riga. Interviews with an experts – reveal major problems in the system of waste management. They mostly concern lack of interest in reaching EU directive requirements, legislation and profitability. The quantitative study explored that only part (11% in Riga) of the citizens is taking in a regular recycling. And for this reason it is considered as a marginal group not as a considerable part of society. One of the tasks was to understand the barriers and reasons for participation in the recycling. During the study there was developed model of citizen participation in recycling and it was found that institutional dimension for which the government is responsible has a negative impact on citizen participation in recycling. A general conclusion can be drawn that the Riga’s citizens' participation level in recycling is relatively low, which can be explained by the passive development of the city's sustainable waste management.
Citizen's participation in recycling in the context of sustainable development
Keywords: Socioloģija